Análisis y evaluación técnica del sistema de circuito cerrado de televisión (CCTV) del Campus Sur de la Universidad Politécnica Salesiana - Alarcón Villaroel, Andrea Estefania (2016)
At the Salesian Polytechnic University South Campus, we have been several security mishaps to teachers and students, that through the video surveillance network have been solved, but the network is not 100 % optimal since it has shortcomings as: blind spots , wiring disorder, absence of cameras in some areas , among others , so it is important to detect these mistakes on time, in order to the network does not fail in a short term and stop working causing serious problems within the institution. The present technical project aims to analyze the CCTV system implemented in the UPS South Campus, by investigating manufacturers' standards and recommendations, which allowed to obtain a verification tool based on a verification model that summarizes the undertaken activities, by which proceeded to obtain results that allowed the network assessment, therefore it pointed the changes to be performed on the network optimization.